2010
DOI: 10.1037/a0018938
|View full text |Cite
|
Sign up to set email alerts
|

Examining the impact of Culture's consequences: A three-decade, multilevel, meta-analytic review of Hofstede's cultural value dimensions.

Abstract: Using data from 598 studies representing over 200,000 individuals, we meta-analyzed the relationship between G. Hofstede's (1980a) original 4 cultural value dimensions and a variety of organizationally relevant outcomes. First, values predict outcomes with similar strength (with an overall absolute weighted effect size of rho = 0.18) at the individual level of analysis. Second, the predictive power of the cultural values was significantly lower than that of personality traits and demographics for certain outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

32
742
2
20

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 838 publications
(796 citation statements)
references
References 527 publications
32
742
2
20
Order By: Relevance
“…Also, if the GLOBE study and other cultural value surveys are tapping into marginal preferences rather than values, then marginal preferences have already been shown to be important. The GLOBE study, along with hundreds of others (see Taras et al, 2010, for a meta-analytic review), confirmed significant relationships between cultural variables (marginal preferences, as asserted by Maseland-van Hoorn) and dozens of workplace-related outcomes. Perhaps if we explicitly instead of accidentally assess marginal preferences, we can do even better.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Also, if the GLOBE study and other cultural value surveys are tapping into marginal preferences rather than values, then marginal preferences have already been shown to be important. The GLOBE study, along with hundreds of others (see Taras et al, 2010, for a meta-analytic review), confirmed significant relationships between cultural variables (marginal preferences, as asserted by Maseland-van Hoorn) and dozens of workplace-related outcomes. Perhaps if we explicitly instead of accidentally assess marginal preferences, we can do even better.…”
Section: Resultsmentioning
confidence: 83%
“…Socio-economic status, education, income levels, age, and other demographic characteristics might be considered as individual-level moderators, and cultural tightness-looseness, freedom, wealth, and other country-level characteristics should be considered as national-level moderators. Furthermore, the degree of value internalization or value traitedness (Taras, Kirkman, & Steel, 2010) may moderate the relationship between values and practices. Such moderator searches could help resolve (or at least clarify) some of these issues.…”
Section: Potential Moderatorsmentioning
confidence: 99%
“…The effects of cultural differences on individual behaviors and perceptions in the workplace have been well documented, showing the need for a culturally sensitive approach in the diverse workplace (Taras et al 2010a). The effects of culture have been traditionally studied in crossnational context with comparisons made across countries.…”
Section: Discussionmentioning
confidence: 99%
“…6. According to the concept of Gelfand, Nishii and Raver's (2006-as cited by Taras et al 2010) of societal tightness-looseness, significantly stronger effects are found in the case of culturally tighter, rather than looser, countries.…”
mentioning
confidence: 99%
“…Based on a detailed meta-analytical review of the first four dimensions (individualismcollectivism, power distance, uncertainty avoidance, masculinity-femininity) 589 studies totalling over 200000 individuals (Taras, Kirkman, & Steel, 2010)conclude that-1. At the individual level of analysis, the cultural values predict outcomes with similar strength (with an overall absolute weighted effect size of ρ=0.18).…”
mentioning
confidence: 99%